Application of Modern Experimental Technique to Solve Morphological Complexity in Plants Taxonomy - SURANTO SURANTO (Biodiversitas Journal of Biological Diversity, 2000)
Modern taxonomy has two approaches, i.e. classical and experimental taxonomy. Classical taxonomy uses morphological characters, while experimental taxonomy uses broader methods including chemistry, physics and mathematics, in the form of laboratory data that are revealed together with the progress of optical technique (microscope), chemistry methods (chromatography, electrophoresis), etc. Modern taxonomy tends to use series of interrelated data. More data used would result in more validity and give better clarification of taxonomic status. A lot of modern taxonomic data such as palynology, cytotaxonomy (cytology), chemical constituent (chemotaxonomy), isozyme and DNA sequencing were used recently.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKeywords: modern taxonomy, palynology, cytotaxonomy, chemical constituent, isozyme.